Media Framing of President Prabowo Subianto's Overseas Visits: An Analysis of Tempo.co News Coverage - Nurliana; Gemilang Bayu Ragil Saputra; Hi. Nawir, Rahmawati; Nawawi, Adelia Ismayana (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study analyzes how Tempo.co frames President Prabowo Subianto’s overseas visits during the first year of his presidency from 20 October 2024 to 20 October 2025. Using a qualitative approach and Robert M. Entman’s framing model, the research examines four selected news articles identified through purposive sampling. The analysis focuses on four framing dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings show that Tempo.co constructs presidential diplomacy through three dominant frames, namely public accountability, policy criticism, and strategic diplomacy. This indicates that Tempo.co does not merely report diplomatic activities but also actively interprets them as subjects of public scrutiny and political evaluation. The study concludes that media framing plays an important role in shaping public understanding of presidential diplomacy and confirms the relevance of Entman’s framing theory in analyzing contemporary digital political communication in Indonesia.